Comment: Stock Market Reforms - Reilly, Frank K. (Journal of Financial and Quantitative Analysis, 1974)
My remarks are divided into two sections. The first section briefly summarizes the major points of the two papers. I should acknowledge that I agree with almost all of the conclusions by Farrar and Mendelson regarding the reforms which have taken place and the beneficial effects of these reforms. The second section briefly discusses one adverse effect of the institutional market not remedied by the reforms. This adverse consequence is only briefly mentioned by Farrar, while it is discussed by Mendelson, but the full implications are not considered.